On counter-enlightenment, existential irony, and sanctification : essays in the sociology of western art musics - Matras, Judah (Academic Studies Press, 2021)
"This book introduces the topics of Enlightenment, Counter-Enlightenment, and social demography in Western art musics and demonstrates their historical and sociological importance. The essays in this book explore the concepts of "existential irony" and "sanctification," which have been mentioned or discussed by music scholars, historians, and musicologists only either in connection with specific composers' works (Shostakovich's, in the case of "existential irony") or very parenthetically, merely in passing in the biographies of composers of "classical" musics. This groundbreaking work illustrates their generality and sociological sources and correlates in contemporary Western art musics"--